Perbandingan Keefektifan Cornell Notes Method Dan Mind Maps Ditinjau Dari Self Efficacy - Nurul Iman (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
This study aims to examine the comparison of the effectiveness of note taking styles of students who use the cornell notes method and mind maps in terms of student self-efficacy. This type of research is a quasi-experimental study with a pretets-posttest nonequivalent comparison-group design. The population in this study were all eighth grade students of SMPN 1 Sungguminasa. The sample is class VIIIE and VIIIB as the experimental class. Class VIIIE is treated in the form of a note-taking style using cornell notes, while class VIIIB is treated as a note-taking style by mind maps. To test the effectiveness of learning using a paired sample t test. To test the difference in effectiveness using the independent sample t-test. The results of this study are: 1) the cornell notes method is not effective if viewed from the students' self efficacy, 2) mind maps is effective if it is reviewed by students' self-efficacy. 3) There is a difference in effectiveness between the cornell notes method and mind maps in terms of students' self-efficacy where students who record by mind maps get better efficacy scores than students who record by cornell notes method.